2010
DOI: 10.1007/s10815-010-9438-z
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extracts attenuate doxorubicin-induced spermatogenic disorders in conjunction with higher telomerase activity in mice

Abstract: Purpose The aim of this study was to investigate the protective effect of green tea extracts against doxorubicininduced damage in the mouse testes correlating with telomerase activity. Methods Green tea extracts were administered orally. Doxorubicin was coadministered intraperitoneally. These testes were evaluated histologically and the telomerase activity was analyzed. Additional immunostaining was carried out. Results Both the sperm density and sperm motility were significantly increased in green tea extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…The ability of catechins to attenuate DOX toxicity was frequently described. In rat, individual catechins and/or green tea extract exhibited protective effects against DOX-induced cardiovascular abnormalities (16), cardiomyocyte injury (17, 18), brain toxicity (19), and spermatogenic disorders (20). Moreover, catechins are able to inhibit carbonyl reductase 1, the main DOX deactivation enzyme (21), and in this way they enhanced DOX efficacy in tumor-bearing mice (22).…”
mentioning
confidence: 99%
“…The ability of catechins to attenuate DOX toxicity was frequently described. In rat, individual catechins and/or green tea extract exhibited protective effects against DOX-induced cardiovascular abnormalities (16), cardiomyocyte injury (17, 18), brain toxicity (19), and spermatogenic disorders (20). Moreover, catechins are able to inhibit carbonyl reductase 1, the main DOX deactivation enzyme (21), and in this way they enhanced DOX efficacy in tumor-bearing mice (22).…”
mentioning
confidence: 99%
“…Generally, the results of DXR administration in testes are; i) thickening of the basal lamina of seminiferous tubules [33] , ii) vacuolisation and/or damages in the Sertoli cells [28,33,34] , iii) degeneration of spermatogonia formed around the nuclei by nuclear condensation of spermatogonia with cytoplasmic content characterised by apoptosis [4] , iv) prominent germ cell loss [28,35] , v) reduction of seminiferous tubule size [35] , vi) a mild inhibition of sperm release due to atrophy of the tubulus seminiferus [6,28,33] , vii) necrosis, degeneration, desquamation, disorganisation, spermatogonial loss due to direct effect of interstitial oedema and congestion in the germ cells [33] , and viii) eventually testicular atrophy allowing Sertoli cells survival only [28] . The findings in testicular tissue revealed that the DXR causes apoptosis due to testicular toxicity as accompanied by the enlargement and severe vacuolisation of interstitial tissue in the interstitial space and a severe vacuolisation and fibrinoid debris in the tubulus seminiferous [4,35] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings in testicular tissue revealed that the DXR causes apoptosis due to testicular toxicity as accompanied by the enlargement and severe vacuolisation of interstitial tissue in the interstitial space and a severe vacuolisation and fibrinoid debris in the tubulus seminiferous [4,35] .…”
Section: Discussionmentioning
confidence: 99%
“…However, co administration of green tea extract with the insecticides antagonizes their reproductive toxicity and oxidative damage (Tarek et al, 2014). Green tea extracts also exert protective effects against doxorubicin-induced spermatogenic disorders in increasing sperm density and motility and attenuating germ cell damage (Sato et al, 2010).…”
Section: Ameliorative Effect On Reproductive Toxicity and Testicular mentioning
confidence: 99%